2018
DOI: 10.1177/2319714518788387
|View full text |Cite
|
Sign up to set email alerts
|

Subsidiary Innovation in a Developing Economy: Towards a Comprehensive Model and Directions for Future Research

Abstract: With the internationalization of innovation, multinational enterprise (MNE) subsidiaries have been found to play a critical role in product and process innovation. Deriving from a rich and diverse subsidiary innovation (SI) literature, this article attempts to develop a comprehensive model to study the factors that impact SI in a developing economy by devising three macro constructs, namely, (a) local environment (LE), (b) subsidiary traits (ST) and (c) headquarters (HQ) strategy (HS). The 15 factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 118 publications
(182 reference statements)
0
8
0
Order By: Relevance
“…Innovation was described in the literature as the ability of a firm to introduce new or improved products, processes, services and marketing approaches to meet market needs (Lawson & Samson, 2001). Past literature indicated that innovation is vital for strengthening brand power and achieving success in the presence of emerging competition (Betaraya et al, 2018; Yam et al, 2004). According to Hanaysha and Hilman (2015), firms have recently experienced momentous challenges with regards to the sustainability practices of their businesses; and for this reason, innovation represents the main strategy to overcome them.…”
Section: Introductionmentioning
confidence: 99%
“…Innovation was described in the literature as the ability of a firm to introduce new or improved products, processes, services and marketing approaches to meet market needs (Lawson & Samson, 2001). Past literature indicated that innovation is vital for strengthening brand power and achieving success in the presence of emerging competition (Betaraya et al, 2018; Yam et al, 2004). According to Hanaysha and Hilman (2015), firms have recently experienced momentous challenges with regards to the sustainability practices of their businesses; and for this reason, innovation represents the main strategy to overcome them.…”
Section: Introductionmentioning
confidence: 99%
“…Under such factors, eventually, subsidiaries may develop specific capacities over time, moving from applying external innovation to driving innovation. In such cases, resulting innovation may also be useful in headquarters [47,48]. Multiple embeddedness also includes universities, suppliers, customers, institutions and other subsidiaries, establishing a large number of stable and profitable local connections [18], which favor open innovation initiatives [3].…”
Section: Structural and Behavioral Contextsmentioning
confidence: 99%
“…The subsidiary's leadership stands out as an essential factor for innovation [18,48], which should rely on a culture focused on innovation [26]. Leadership may require ascending, horizontal and descending strategic positioning.…”
Section: Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Multinationals from leading emerging economies like China, India, Malaysia, Vietnam, Turkey and Brazil have achieved dominant positions in many industries in terms of market share (Awate et al, 2012). Looking at multinational enterprises (MNEs) from emerging countries like Huawei, TCS, AirAsia and Embraer, it is important to note that the innovation capabilities of emerging market economies are driven, not only by their own firms but also by the subsidiaries of advanced country MNEs (Mudambi, 2011;Betaraya et al, 2018). There are only handful of studies conducted on internationalization of emerging market multinationals (Paul and Gupta, 2014), some of these studies lacks empirical evidence (Yaprak and Karademir, 2010;Gaur and Kumar, 2010) or present emerging market multinationals as facilitators to the developed market multinationals (Yaprak and Karademir, 2011).…”
mentioning
confidence: 99%